Sozialethische Probleme des Lebensschutzes (Społeczno etyczne problemy ochrony życia - tekst po niemiecku) (Diametros, 2010)
The Social Doctrine of the Church investigates the structural and institutional prerequisites for the success of human life. This endeavor is focused on guidelines for a beneficial and just social order which allows human beings to enjoy a person-centered development. Until very recently, Christian Social Doctrine has displayed a remarkable blindness towards the ethical problem of the protection of life at the beginning and at the end of the human life cycle. Little was said about abortion, euthanasia, research on human embryonic stem cells, cloning and Pre-Implantation Diagnostics. As long as the legal and constitutional frameworks of civilized modern states protected human rights, especially with a firm injunction against abortion and euthanasia, the issue of the protection of life did not require the undivided attention of Christian Social Doctrine. All this changed with the dawn of the 1970s. Christian Social Doctrine must underscore the key prerequisites of the rule of law in democratic societies: the prohibition of the private use of force and the killing of innocent human beings.
Keywords: abortion; Christian Social Doctrine; rule of law